Transformational leadership and organizational performance in a Local Educational Management Unit in Peru (Gestionar: revista de empresa y gobierno, 2022)
This article sought to determine how transformational leadership influences organizational performance in the Local Educational Management Unit of Chiclayo, Peru. A quantitative approach was followed, applied research, with a non-experimental design, census sampling was used, determining 113 collaborators, for data collection the survey technique was used. The results obtained indicate that 76.99% of the sample disagrees regarding the existence of a charismatic leadership, this weakness affects the operators and therefore the entire organization. Weaknesses were found in the different dimensions: 1) performance (47.78% disagree); 2) efficiency and effectiveness (81.41%, disagree); 3) continuity (53.11%, disagree); 4) use of resources (67.26% disagree). It was concluded, there are serious weaknesses with respect to organizational performance in the institution
Keywords: leadership; transformation; performance; organization